Physiologic-Based Cord Clamping Maintains Core Temperature vs. Immediate Cord Clamping in Near-Term Lambs - Blank, Douglas A.; Crossley, Kelly J.; Kashyap, Aidan J.; Hodges, Ryan J.; DeKoninck, Philip L. J.; McGillick, Erin V.; Rodgers, Karyn A.; te Pas, Arjan B.; Hooper, Stuart B.; Polglase, Graeme R. (Frontiers in Pediatrics, 2020)
Background: Physiologic-based cord clamping (PBCC) involves deferring umbilical cord clamping (UCC) until after lung aeration. It is unclear if infant is at risk of becoming hypothermic during PBCC. Objectives: To test if PBCC would maintain core temperature more effectively than immediate cord clamping (ICC). Design: At 0.93 gestation, fetal lambs were surgically exteriorized and instrumented from pregnant ewes under general anesthesia. Prior to the start of the experiment, lambs were thoroughly dried, placed on hot water bottles, and core temperature was continuously monitored using a rectal thermometer. PBCC lambs (n=21), received intermittent positive pressure ventilation (iPPV) for ≥5 minutes prior to UCC. In ICC lambs (n=23), iPPV commenced within 60 seconds after UCC. iPPV was provided with heated/humidified gas. Lambs were moved under a radiant warmer after UCC. Additional warmth was provided using a plastic overlay, hairdryer, and extra water bottles, as needed. Two-way mixed and repeated measures one-way ANOVAs were used to compare temperature changes between and within a single group, respectively, over time. Results: Basal fetal parameters including core temperature were similar between groups. ICC lambs had a significant reduction in temperature compared to PBCC lambs (p<0.001), evident by 1 minute (p=0.002). ICC lambs decreased temperature by 0.51°C (±0.42) and 0.79°C (±0.55) at 5 and 10 minutes respectively (p<0.001). In PBCC lambs, temperature did not significantly change before or after UCC (p=0.4 and p=0.3, respectively). Conclusions: PBCC stabilized core temperature at delivery better than ICC in term lambs. Hypothermia may not be a significant risk during PBCC.